PENGGUNAAN MEDIA PAPAN STATISTIKA UNTUK MENINGKATKAN PEMAHAMAN KONSEP MATEMATIKA SISWA KELAS VI SEKOLAH DASAR - Lubis, Nuradilah; Arief Aulia Rahman; Irvan, Irvan; Manik, Hamdi Yanti (OMEGA: Jurnal Keilmuan Pendidikan Matematika, 2025)
The purpose of the study was to determine the effect of the Statistics Board media on students' conceptual understanding of Statistics material in class VI of SDN 066054 Medan. The research used was classroom action research which aims to improve students' conceptual understanding of Mathematics learning. The place of implementation of the research was at SDN 066054 Medan. The samples taken were all students in class VI, consisting of 18 students, including 6 boys and 12 girls. This study used the classroom action research (CAR) method with two cycles. Based on the results of the study, by using the Statistics Board media, there was an increase in students' understanding in understanding the concept of Statistics consisting of Mean, Median, and Mode. This study concludes that learning methods using media can improve students' understanding in understanding learning concepts.